APLIKASI SELEKSI CALON KEPALA SEKOLAH DENGAN METODE SMARTER (Simple Multi –Attribute Rating Technique Exploiting Ranks) DAN ORESTE - Cucu Tohir (JUTEKIN (Jurnal Teknik Informatika), 2017)
Today, the need for information is very important for everyone. Rapid information obtained and an efficient use of time is one factor that is needed by any organization or company to progress the institution. The progress of a school can not be separated from the influence of the principal. The principal position is for a teacher's career development. There fore we need qualified human resources as well as teachers who have the potential and achievement to become principals. Decisions determining the principal candidates in Kudat District Education Office is relatively difficult because there are many criteria that influence, and most of these criteria are criteria that are subjective though there are also criteria that are objective which can be seen from the administrative assessment. A principal ideal maximally expected to master the overall assessment criteria. In this final and made an application designed to help Kudat District Education Office in determining the ranking of candidates based on the value of the principal on certain criteria that the selection of the participants is a participant teachers as Kudat District selection. The method used to determine eligibility and priority in the selection of candidates for these principals to use Simple Multi-Attribute Rating Technique Exploiting Ranks (SMARTER) and Oreste.Keywords: Criteria, Assessment Administrative, Application, Simple Multi-Attribute Rating Technique Exploiting Ranks (SMARTER) and Oreste.